Analisa Audit Upaya Efisiensi Energi di PT. Telkom Witel Unit Network Area dan IS Operation - Ruwah Joto; Sukamdi; Pratama Aditya (Politeknik Negeri Malang, 2022)
The increasing use of energy, in line with the development of the economy and industry, it is also necessary to realize the importanceof saving energy on the consumption side. Energy conservation is an increase in the efficiency of energy used or energy saving processes.This process includes an energy audit, which is a method for calculating the energy consumption level of a building or buildings, the resultsof which will be compared with existing standards to then look for solutions to save energy consumption if the energy consumption levelexceeds existing standards. The method used for research in this final project uses a walking audit by collecting data based on current,voltage, and power measurements. The data will be used to determine the analysis of the consumption of electrical energy used in the PT.Telkom Witel Unit Network and IS Operation Malang. Calculation of the IKE value (Energy Consumption Intensity) of the Malang City STObuilding for the results from the account data, the results are 479.14 kWh/m²/year. As for the IKE value from the measurement, the result is443.5 kWh/m²/Year 2, the value of the IKE is very inefficient from the standard compared to the ASEAN USAID standard in 1987, becausethe total power per year is not proportional to the existing building area. The lighting strength value after the recommendation is according tothe standard by replacing the lamp with a large lumen value, while in the cooling system the calculation of the BTUH requirement for eachroom is compared to the BTU AC (Air conditioner).